2020
DOI: 10.1161/circulationaha.119.040747
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis of Neonatal Regenerative Myocardium Revealed Important Roles of Checkpoint Kinase 1 via Activating Mammalian Target of Rapamycin C1/Ribosomal Protein S6 Kinase b-1 Pathway

Abstract: Background: In mammals, regenerative therapy after myocardial infarction is hampered by the limited regenerative capacity of adult heart, whereas a transient regenerative capacity is maintained in the neonatal heart. Systemic phosphorylation signaling analysis on ischemic neonatal myocardium might be helpful to identify key pathways involved in heart regeneration. Our aim was to define the kinase-substrate network in ischemic neonatal myocardium and to identify key pathways involved in heart regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…We evaluate our approach on previously published phosphoproteomic data. This includes data sets from more than one hundred public repositories [4] and additionally validate these results on recently published data [26, 27, 28, 29, 30] and in case of cross-linking data we use previously published data to evaluate our transfer learning approach [31, 32, 33].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We evaluate our approach on previously published phosphoproteomic data. This includes data sets from more than one hundred public repositories [4] and additionally validate these results on recently published data [26, 27, 28, 29, 30] and in case of cross-linking data we use previously published data to evaluate our transfer learning approach [31, 32, 33].…”
Section: Introductionmentioning
confidence: 61%
“…For validation we use five data sets [28, 29, 30, 26, 27]. For each data set, we used the original search results from MaxQuant alongside the raw spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the proliferation and regeneration ability of heart tissue basically disappears around the 7 th day of development, and the cell cycle of cardiomyocytes no longer exists, with only a very small proliferation rate remaining [ 12 14 ]. The underlying mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the adult zebrafish, the CMs of neonatal mice possess the proliferative capability and maintain the competence to renovate their damaged cardiac muscle tissue during the first 7 days of life [11,12]. Convincing evidence shows that heart regeneration in neonatal mice is achieved by cardiomyocyte proliferation and the cardiac developmental program for self-renewal [12][13][14]. The underlying mechanisms of neonatal cardiac proliferation remain largely unclear, but the related research is of crucial significance for discovering therapeutic targets for cardiomyocyte regeneration and cardiac repair.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples from different regions of the lungs were subjected to protein extraction and digestion according to previous methods. 16 The peptides were labelled, mixed and desalted by tC18 Sep-Pak column (Waters, USA).…”
Section: Protein Sample Preparation Digestion and Tandem Mass Tag mentioning
confidence: 99%